國內大學學習預警資訊系統研究： 發展現況與侷限 Students' Early Alert Systems in Taiwanese Universities: A Study of Current Uses and Restrictions - 謝佩珊 Pei-Shan Hsieh; 石美倫 Meilun Shih (National Taiwan Normal University, 2020)
學生學習預警資訊系統被認為是評量學生學習成效、預測學習困擾、輔導高危險群學生的有力機制，尤其近年來新興資訊技術的進步，使學習預警資訊系統在規模和作法上都有所突破。國內各大學發展學習預警資訊系統已超過 10 年，普及率也相當高，但是相較於國外既有的深入性和檢討性研究，目前針對國內現有學習預警機制與系統運作的著述仍然頗為零散，而該系統在功能上的敏感性及資料上的隱密性，也讓各校之間缺乏相關資訊交流。因此，本研究主要透過文獻探討、訪察和訪談等方法，針對國內目前 56 所公私立一般大學學習預警資訊系統的現行運作情況進行概括性調查。研究發現，目前各校多已建立了學期間、即時和特殊預警等不同機制，系統使用率在許多大學也都達到半數課程以上，但在實際使用上常面 臨教師反彈和後續追蹤不易等問題。建議未來各校應以加強跨單位合作、提升系統使用成效評估，以及提供更多元的預警指標為方向，進一步落實學習預警資訊系統之功能及使用效益。 The development of students' early alert systems (EAS), or students' learning alarm systems, has long been discussed by administrators and researchers in higher education. They are considered a powerful mechanism for evaluating students' learning effectiveness, predicting potential learning difficulties, and identifying academically at-risk students. The rapid growth of information technology has made the EAS advanced in scale and practice. However, although most universities in Taiwan have established similar preventive systems or mechanisms, few studies have focused on exploring actual uses of and possible restrictions on existing EAS. Therefore, the main purpose of this study was to outline the current situation of EAS in Taiwanese universities. We explored the following questions: (1) What types of EAS have been established in universities in Taiwan? (2) What are the main functions and mechanisms of the current EAS? (3) What are the actual uses of EAS in universities? (4) What are the possible restrictions on and solutions for using EAS? Data were gathered from 56 public and private universities in Taiwan. Experts familiar with or in charge of EAS design, development, and use in these universities were interviewed by telephone or face-to-face. We found that although the utility rate of EAS in most universities tended to be high, faculty resistance and difficulty in follow-up assessments on EAS utilization were the two common restrictions that occurred across campuses. To enhance the use effectiveness of EAS, faculty and administrators from both departmental and institutional levels should be involved. In addition, this study suggested that in the future, universities must attempt to strengthen collaboration among units related to EAS, improve the evaluation of EAS effectiveness, and provide additional early alert indicators of students' academic performance.